IMPLEMENTATION OF THE ARIAS MODEL IN ICT SUBJECTS IN INCREASING THE QUALITY OF STUDENT LEARNING - Basrul Abdul Majid; Achmad Andrian; Khairan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
The aim of this study was to analyze how the ARIAS framework influences learning in the field of information and communication technology (ICT). This study used a Quasi Experiment with One Control Group Pree-Test Post-Test Design, with the actual test as the instrument. The findings show that the ARIAS learning model has a significant impact on ICT education standards at SMKN 1 Sawang in South Aceh. The results obtained are P = 0.569 > = 0.05 which means H1 is accepted and H0 is rejected; In particular, the ARIAS model predicts that class X students will achieve posttest learning outcomes higher than the average of 69.99 if at least 20 students complete learning with a minimum score of 76.09%. This research shows that class X students of SMKN 1 Sawang Aceh Selatan have succeeded in applying the ARIAS model to their ICT education.